Institutional corporate social responsibility (CSR) practices: the influence of leadership styles and their perceived ethics and social responsibility role - Ho, Jo Ann; Ang, Yen Hui; Tee, Keng Kok (Universiti Putra Malaysia Press, 2015)
This paper investigates leader's perceptions of ethics and social responsibility (PRESOR) on organisation's institutional CSR practices. The results indicate that while the managers in this study perceive that ethics and social responsibility play an important role in determining the organisation's long-term and short-term gains, they do not think that ethics and social responsibility are the only important factors in determining firm's profitability and survival, as indicated by the non-significant results of the PRESOR (social responsibility and profitability) dimension. Another objective was to determine the types of leadership style in influencing the adoption and practices of CSR. As oppose to many previous studies, the results indicate that among the leadership styles, transactional leadership influences institutional CSR practices, while transformational leadership does not. This finding implies that for CSR practices to be implemented, leaders need to use rewards, rules and regulations in a Malaysian context. In other words, in order to institutionalise CSR practices in Malaysia, corporations should start by introducing extrinsic incentives.